FINANCIAL KNOWLEDGE HASIL PENDAPATAN TERHADAP PERILAKU PERENCANAAN DANA PENSIUN JAJARAN APARATUR DS. MANGGIS KEC. MOJOSONGO KAB. BOYOLALI - Sopiin; Aris Basuki; Natalina Kristiani; Yulianto; Sertar Andrew Christian B. Panjaitan; Sertar Farhan Fadhilah Iriandi (JURNAL NAGARA BHAKTI, 2024)
Based on existing facts in the field, it shows that there are still those who are less serious in planning their finances as in the PKM that Sundjaja (2015) has done on financial planning for employees at private educational institutions in Bandung, it shows that there are still 27% of 52 people or around 14 people who have not made a monthly financial budget, and still cause difficulties in managing their finances in old age or retirement, the purpose of delivering financial knowledge and preparing finances at the time before retirement so that after retirement they can be more prosperous and calmer. Their understanding of post-retirement income to be conveyed through counseling by the PKM Team from the Kordos Akmil Manhan Study Program in the implementation of PKM to carry out counseling and discussions related to the topic of discussion regarding Financial Knowledge of Income Results on Retirement Fund Planning Behavior of Manggis Village Mojosongo Sub District Boyolali Regency. Financial knowledge planning that a person has can make them wise in managing their finances and also provide benefits to the individual economy. The higher the level of financial knowledge a person has, the lower the level of external locus of control they have. This is because they will be more able to manage their finances well.